Clinical diagnosis of Q fever by targeted next-generation sequencing for identification of Coxiella burnetii - Shaohua Zhan; Haoyuan Jin; Hanbing Ji; Xin Hou; Jing Li; Ye Zhang; Jiajia Zheng; Liyan Cui (BMC Infectious Diseases)
Abstract Purpose Q fever is a zoonotic bacterial disease caused by Coxiella burnetii. Due to its variable and non-specific clinical symptoms, the disease is often overlooked and underreported. To date, the identification of C. burnetii as the causative pathogen of Q fever using targeted next-generation sequencing (tNGS) has not been previously documented. Methods tNGS was performed on patients with acute fever of unknown etiology, and qPCR was confirmed for C. burnetii infection. Results tNGS was performed on 112 patients with acute fever of unknown etiology at Peking University Third Hospital between March 27 and September 20, 2024. C. burnetii was identified in blood samples from five patients, leading to a clinical diagnosis of Q fever. These diagnoses were subsequently confirmed by qPCR at the Beijing CDC. The mean age of the patients was 39.6 years (range: 32–59 years). Although blood cultures were negative, elevated infection markers (CRP, PCT, and ferritin) and liver enzymes (ALT, AST, GGT, ALP, and LDH) were observed. No epidemiological links to Q fever were identified in these cases. All five patients were treated promptly with oral doxycycline (0.1 g twice daily for 2 weeks) and discharged in improved health. Conclusions tNGS is a promising and significant tool for rapidly detecting C. burnetii infection.